A case of pembrolizumab-induced severe DKA and hypothyroidism in a patient with metastatic melanoma. (5th March 2019) - Hakami, Osamah A; Ioana, Julia; Ahmad, Shahzad; Tun, Tommy Kyaw; Sreenan, Seamus; McDermott, John H
Summary: Immune checkpoint inhibitors (ICIs) have revolutionised cancer therapy and improved outcomes for patients with advanced disease. Pembrolizumab, a monoclonal antibody that acts as a programmed cell death 1 (PD-1(PDCD1)) inhibitor, has been approved for the treatment of advanced melanoma and other solid tumours. Immune-related adverse events (irAEs) including endocrinopathies have been well described with this and other PD-1 inhibitors. While hypothyroidism and hyperthyroidism, and less commonly hypophysitis, are the most common endocrinopathies occurring in patients treated with pembrolizumab, the incidence of type 1 diabetes mellitus (T1DM) was low in clinical trials. We report a case of pembrolizumab-induced primary hypothyroidism and T1DM presenting with severe diabetic ketoacidosis (DKA). A 52-year-old male patient was treated with pembrolizumab for metastatic melanoma. He presented to the emergency department with a 1-day history of nausea and vomiting 2 weeks after his seventh dose of pembrolizumab, having complained of polyuria and polydipsia for 2 months before presentation. He had been diagnosed with thyroid peroxidase (TPO) antibody-negative hypothyroidism, requiring thyroxine replacement, shortly after his fifth dose. Testing revealed a severe DKA (pH: 6.99, glucose: 38.6 mmol/L, capillary ketones: 4.9 and anion gap: 34.7). He was treated in the intensive care unit as per the institutional protocol, and subsequently transitioned to subcutaneous basal-bolus insulin. After his diabetes and thyroid stabilised, pembrolizumab was recommenced to treat his advanced melanoma given his excellent response. This case highlights the importance of blood glucose monitoring as an integral part of cancer treatment protocols composed of pembrolizumab and other ICIs. Learning points: The incidence of T1DM with pembrolizumab treatment is being increasingly recognised and reported, and DKA is a common initial presentation. Physicians should counsel patients about this potential irAE and educate them about the symptoms of hyperglycaemia and DKA. The ESMO guidelines recommend regular monitoring of blood glucose in patients treated with ICIs, a recommendation needs to be incorporated into cancer treatment protocols for pembrolizumab and other ICIs in order to detect hyperglycaemia early and prevent DKA.